2022
DOI: 10.1093/pnasnexus/pgac024
|View full text |Cite
|
Sign up to set email alerts
|

Exploration of immunological responses underpinning severe fever with thrombocytopenia syndrome virus infection reveals IL-6 as a therapeutic target in an immunocompromised mouse model

Abstract: Dabie bandavirus (previously severe fever with thrombocytopenia syndrome virus; SFTSV) is an emerging tick-borne bunyavirus responsible for severe fever with thrombocytopenia syndrome (SFTS), a disease with high case fatality that is characterised by high fever, thrombocytopenia, and potentially lethal haemorrhagic manifestations. Currently, neither effective therapeutic strategies nor approved vaccines exist for SFTS. Therefore, there remains a pressing need to better understand the pathogenesis of the diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Furthermore, in 2022, it was recommended for the management of patients with severe COVID-19 in South Korea ( Korean Society of Infectious Diseases 2022 ). In a recent SFTS animal study, the administration of an anti-IL-6 antibody, when disease progressed from mild to moderate, significantly increased the survival of the infected animals ( Bryden et al, 2022 ). The above-mentioned studies support a therapeutic strategy of inhibiting IL-6 pathways in patients with SFTS.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…Furthermore, in 2022, it was recommended for the management of patients with severe COVID-19 in South Korea ( Korean Society of Infectious Diseases 2022 ). In a recent SFTS animal study, the administration of an anti-IL-6 antibody, when disease progressed from mild to moderate, significantly increased the survival of the infected animals ( Bryden et al, 2022 ). The above-mentioned studies support a therapeutic strategy of inhibiting IL-6 pathways in patients with SFTS.…”
Section: Discussionmentioning
confidence: 72%
“…The development of SFTS has been associated with the significant upregulation of proinflammatory cytokines, including high levels of interferon (IFN)γ and interleukin (IL)-6 ( Yoo et al, 2021 ). Nonetheless, anti-IL-6 antibodies significantly increased the survival of mice with SFTS ( Bryden et al, 2022 ). Herein, we report for the first time, the early application of an anti-IL-6 antibody in a patient with SFTS.…”
Section: Introductionmentioning
confidence: 91%
“…The entrapped molecules are mainly involved in host type I IFN induction and signaling pathways, such as those involving the protein kinase TBK1, RIG-I, interferon regulatory factor (IRF)-3, IRF-7, STAT1, and STAT2 [ 13 , 14 , 15 , 16 , 17 ]. Furthermore, in vivo studies indicated that recombinant SFTSV that lacked NSs had limited pathogenicity in aged ferrets and type I IFN receptor-deficient (IFNAR −/− ) mice [ 18 , 19 ]. Therefore, NSs are the virulence factors of SFTSV.…”
Section: Introductionmentioning
confidence: 99%
“…4 Several lines of evidence had supported cellular immunosuppression and immune paralysis that ensued by SFTSV infection, which led to overproduction of pro-and anti-inflammatory mediators. 5 Systemic inflammatory response syndrome and compensatory anti-inflammatory response syndrome resulting from SFTSV infection also increase susceptibility to coinfections. 6,7 Coinfection in severe cases of SFTS had been reported, with invasive pulmonary aspergillosis (IPA) as the most frequent pathogenic infection.…”
Section: Introductionmentioning
confidence: 99%
“…In severe SFTS patients, coinfection readily occurs as a result of the dysregulated immune system of the host 4 . Several lines of evidence had supported cellular immunosuppression and immune paralysis that ensued by SFTSV infection, which led to overproduction of pro‐ and anti‐inflammatory mediators 5 . Systemic inflammatory response syndrome and compensatory anti‐inflammatory response syndrome resulting from SFTSV infection also increase susceptibility to coinfections 6,7 …”
Section: Introductionmentioning
confidence: 99%